2004
DOI: 10.1128/mcb.24.16.6980-6992.2004
|View full text |Cite
|
Sign up to set email alerts
|

Activation of RBL-2H3 Mast Cells Is Dependent on Tyrosine Phosphorylation of Phospholipase D2 by Fyn and Fgr

Abstract: Both phospholipase D1 (PLD1) and PLD2 regulate degranulation when RBL-2H3 cells are stimulated via the immunoglobulin E receptor, FcRI. However, the activation mechanism for PLD2 is unclear. As reported here, PLD2 but not PLD1 is phosphorylated through the Src kinases, Fyn and Fgr, and this phosphorylation appears to regulate PLD2 activation and degranulation. For example, only hemagglutinin-tagged PLD2 was tyrosine phosphorylated in antigen-stimulated cells that had been made to express HA-PLD1 and HA-PLD2. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 65 publications
1
49
0
Order By: Relevance
“…As shown in Figures 5a and b, the F replacement of Y 169 was enough to eliminate PLD activity, whereas Y 179 was dispensable for PLD2 catalysis since mycPLD2 Y179F and DY 179 were fully active enzymes. The same substitution of Y 165 had no effect on PLD2 activity, as described earlier (Choi et al, 2004).…”
Section: Preparation Of Mutant Seriesmentioning
confidence: 82%
See 2 more Smart Citations
“…As shown in Figures 5a and b, the F replacement of Y 169 was enough to eliminate PLD activity, whereas Y 179 was dispensable for PLD2 catalysis since mycPLD2 Y179F and DY 179 were fully active enzymes. The same substitution of Y 165 had no effect on PLD2 activity, as described earlier (Choi et al, 2004).…”
Section: Preparation Of Mutant Seriesmentioning
confidence: 82%
“…As for the correlation between PLD2 and tyrosine phosphorylation, it has been previously shown that PLD2 interacts with c-Src and other tyrosine kinases (Slaaby et al, 1998;Ahn et al, 2003;Choi et al, 2004), and the protein tyrosine phosphatase 1b (PTP1b) (Horn et al, 2005). Since the ternary complex PLD2/Grb2/ PTP1b exists in vivo (Horn et al, 2005), it is possible that total tyrosine phosphorylation of PLD2 may also be regulated in a PLD2-Y 179 /Grb2-SH3-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, others have show that PLD2 can be phosphorylated on tyrosine by Fyn and Fgr kinases in mast cells [24]. This phosphorylation is concomitant with PLD2 activation and cell degranulation [24].…”
Section: Introductionmentioning
confidence: 99%
“…The specific roles of Lyn and Fyn in regulating Fc⑀RI-induced mediator secretion in the RBL-2H3 cell line are still being elucidated. A recent study by Choi et al (22) determined that the Src family kinases Fyn and Fgr positively regulate degranulation in RBL-2H3 cells, at least in part, by activating phospholipase D 2 . In the current study, we stably transfected the unique domain of Lyn into RBL-2H3 mast cells and examined the consequences on Fc⑀RI-induced signal transduction and mediator secretion to further define the role of the unique domain of Lyn in mast cell secretion.…”
Section: Regulation Of Rat Basophilic Leukemia-2h3 Mast Cellmentioning
confidence: 99%